2005
DOI: 10.1128/mcb.25.15.6559-6569.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human SRCAP and Drosophila melanogaster DOM Are Homologs That Function in the Notch Signaling Pathway

Abstract: The putative ATPase chromatin-remodeling machine SRCAP was identified in a yeast two-hybrid protein screen by interaction with the histone acetylase CBP. SRCAP is implicated in the transcriptional coactivation of cyclic AMP-and steroid-dependent promoters, but no natural chromosomal targets for SRCAP regulation have been identified. DOM is the unique SRCAP homolog in Drosophila melanogaster. The goal of this study was to test whether SRCAP is a functional homolog of DOM and to identify potential activities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 47 publications
(60 reference statements)
3
74
0
Order By: Relevance
“…Domino-A is more restricted in expression than domino-B, and domino-B is likely the major domino product expressed in wing disks (47). Previous studies indicated that a domino mutation increased the severity of the N nd-1 mutant phenotype, suggesting that domino-B participates in Notch signaling at the wing margin, and cultured cell transfection experiments with mammalian SRCAP suggest that it supports transcriptional activation by Notch (16). Figure 8 shows that, similar to the previously reported effect of the dom 7 mutation, the dom 1 mutation increased the severity of the N nd-1 mutant phenotype.…”
Section: The Genetic Analysis Indicates That Nipped-asupporting
confidence: 77%
“…Domino-A is more restricted in expression than domino-B, and domino-B is likely the major domino product expressed in wing disks (47). Previous studies indicated that a domino mutation increased the severity of the N nd-1 mutant phenotype, suggesting that domino-B participates in Notch signaling at the wing margin, and cultured cell transfection experiments with mammalian SRCAP suggest that it supports transcriptional activation by Notch (16). Figure 8 shows that, similar to the previously reported effect of the dom 7 mutation, the dom 1 mutation increased the severity of the N nd-1 mutant phenotype.…”
Section: The Genetic Analysis Indicates That Nipped-asupporting
confidence: 77%
“…Recent reports have shown that using genetic studies in flies, the Nipped-A/Tra1/TRRAP proteins and the SRCAP/ DOM proteins are required for the activity of Notch through its coactivator protein, mastermind, during wing development and are key component of the Tip60 histone acetylase complex (20,26,44). The Notch intracellular domain was not identified among the proteins associated with Nipped-A/Tra1/TRRAP and SRCAP/DOM in the Tip60 complexes (9).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies using the fly system have shown that TRRAP and domino have functions in Notch signaling. However, findings do not rule out the possibility that TRRAP and domino can also act independently of Tip60 (20,26). Cellular responses to DNA damage also involve the HAT Tip60, as the overexpression of a dominant negative HAT-defective Tip60 mutant decreases both DNA repair and apoptosis upon the induction of DNA double-stranded breaks (12,33,69).…”
mentioning
confidence: 88%
“…That such an integral NuA4/TIP60 complex component displays phenotypes similar to reptin mutants suggests to us that Reptin functions through the fly TIP60 complex. Domino protein is similar to p400 and to SRCAP in mammals and to Swr1 in yeast (Eissenberg et al 2005). Swr1 has recently been shown to exchange the variant histone H2A.Z (Htz1 in yeast) for H2A in nucleosomes (Krogan et al 2003;Kobor et al 2004;Mizuguchi et al 2004).…”
Section: Discussionmentioning
confidence: 99%